Severe Acute Respiratory Infections With Influenza and Noninfluenza Respiratory Viruses: Yemen, 2011-2016 - Al Amad, Mohammad Abdullah (Inquiry, 2019)
In 2010, Yemen started the surveillance for severe acute respiratory infections (SARIs) by establishing 2 sentinel sites in Sana’a and Aden city. This study aims to determine the proportions of influenza and noninfluenza viruses among SARI patients and to determine the severity of SARI and its associated factors. The data of SARI patients who were admitted to SARI surveillance sites at Al Johory hospital in Sana’a and Al Wahdah hospital in Aden city during the period 2011-2016 were analyzed. The proportions of positive influenza viruses (type A, B) and noninfluenza viruses (respiratory syncytial, adenovirus, human parainfluenza, and human metapneumovirus), intensive care unit (ICU) admission rate, and fatality rate among SARI patients were calculated. A total of 1811 of SARI patients were admitted during 2011-2016. Of those, 78% were <15 years old. A total of 89 (5%) patients had influenza viruses and 655 (36%) had noninfluenza viruses. The overall ICU admission rate was 40% and the case-fatality rate was 8%. Infection by influenza type (A, B) and mixed (adenovirus, human parainfluenza) was significantly associated with lower ICU admission. Age <15 years old, infection with influenza B, pre-existence of chronic diseases, and admission to Aden site were significantly associated with higher fatality rate among patients. In conclusion; SARI patients in Yemen had a high ICU admission and case-fatality rates. Influenza type B, chronic diseases, and admission to Aden site are associated with higher fatality rate. Expanding surveillance sites and panel of laboratory tests to involve other pathogens will help to provide accurate diagnosis for SARI etiology and give more comprehensive picture. Training staff for SARI case management will help to reduce severe outcomes.